2012
DOI: 10.1111/j.1600-6143.2011.03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Graft Outcome and Quality (After Transplantation) From Uncontrolled Deceased Donors After Cardiac Arrest

Abstract: The use of uncontrolled deceased donors after cardiac arrest (uDDCA) has been developed in France to compensate for organ shortage. The quality of these kidneys remains unclear. We analyzed kidney graft function and histology from 27 uDDCA and compared them with kidneys from 30 extended criteria donors (ECD) and from 24 simultaneous pancreas kidney (SPK) donors as a control group of optimal deceased donors. Kidneys from ECD and SPK donors were preserved by static cold storage while kidneys from uDDCA were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
1
32
1
4
Order By: Relevance
“…In the present study, an association between 3‐month interstitial fibrosis and RI at the end of perfusion has been shown. However, it was not higher than in ECD and did not seem to influence graft survival at 1 post‐transplant year as previously shown . The very low rate of PNF and the high kidney survival rate confirmed that using the machine perfusion, it is possible to select uDCD kidneys pre‐operatively and to prevent the deleterious effects of warm ischemia improving renal function after the transplantation.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, an association between 3‐month interstitial fibrosis and RI at the end of perfusion has been shown. However, it was not higher than in ECD and did not seem to influence graft survival at 1 post‐transplant year as previously shown . The very low rate of PNF and the high kidney survival rate confirmed that using the machine perfusion, it is possible to select uDCD kidneys pre‐operatively and to prevent the deleterious effects of warm ischemia improving renal function after the transplantation.…”
Section: Discussionsupporting
confidence: 69%
“…We used a higher cutoff of 1st WIT in the uDCD compared to other studies. 10,11,26 In addition, our 1st WIT is higher in the cDCD compared with the UK. 25 According to our data, when transplanting a uDCD kidney from a 40-year-old donor with a CIT of 12.0 hours and 1st WIT of 25 minutes as compared to a uDCD kidney transplanted with the same donor age, but an increased CIT of 23 hours and 1st WIT of 29.4 minutes, the predicted chance of PNF is reduced to 10.7 % (0.1873-0.1067 × 100 = 8.1% risk difference within uDCD).…”
Section: Discussionmentioning
confidence: 77%
“…Several small clinical studies support that uDCD kidneys perform comparably to expanded criteria donor grafts, 9,11 and the 3-month and 1-year histological assessments of graft biopsies from uDCD and expanded criteria donor grafts revealed no differences in interstitial fibrosis and tubular atrophy. 10 Viglietti et al 26 in France showed longitudinal data from sequential biopsies of transplanted uDCD kidneys. They concluded that in uDCD recipients with a no-flow time of less than 10 minutes, 1-year eGFR and the degree of interstitial fibrosis were similar to those of DBD recipients.…”
Section: Discussionmentioning
confidence: 99%
“…uDCD relates to excellent long-term kidney graft survival, despite an increased incidence of primary nonfunction (PNF) and delayed graft function (DGF) [9][10][11][12][13][14][15][16][17][18][19][20][21]. The results of liver transplantation from uDCD donors are mixed and do not consistently provide similar outcomes compared with livers from donation after brain death (DBD) donors, mainly because of a higher incidence of primary graft dysfunction, graft nonfunction and biliary complications [22][23][24][25][26][27].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…C [3,[9][10][11][12][13][14][15][16][17][18][19][20][21] (kidney) [23][24][25][26][27][57][58][59][60] (liver)…”
unclassified